The Initiation and Early Stages of Postmolt Mineralization in the Blue Crab, Callinectes sapidus - Roer, Robert D.; Dillaman, Richard M. (Frontiers in Marine Science, 2018)
Crabs are encased in a rigid exoskeleton or cuticle that is hardened by the both protein crosslinking and calcification. In order to grow, the exoskeleton must be periodically molted. The two outermost layers of the exoskeleton of crabs are deposited prior to the molt, but remain uncalcified until the animal sheds it old exoskeleton. The inhibition of premolt calcification and initiation of postmolt calcification are effected by biochemical changes in the organic matrix. In the two hours after the molt, sugar moieties are enzymatically altered on cuticular glycoproteins by an N-acetylhexosaminidase secreted by the underlying epithelium. These alterations appear to unmask nucleation sites that allow calcification to commence. The initial deposition of mineral is in the form of amorphous calcium carbonate (ACC). As postmolt calcification continues and the principal layer (endocuticle) is deposited and mineralized, the ACC is largely converted to or overgrown by calcite. Prior to the onset of ACC deposition, silicon has been detected in those areas of the exoskeleton that are about to undergo mineralization. As calcification proceeds, silicon is no longer detected. It is hypothesized that silicon is involved in the stabilization of ACC by destabilizing the crystal lattice of calcite before it undergoes the transition to or is overgrown by crystalline calcite.